2007
DOI: 10.1002/cbdv.200790030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Evaluation of Novel 7‐O‐Modified Genistein Derivatives

Abstract: Two series of genistein (=5,7-dihydroxy-3-(4-hydroxyphenyl)-4H-1-benzopyran-4-one) derivatives with heterocycles were prepared, in which genistein and heterocyclic moieties were separated by C(2) and C(3) spacers. Among the 24 compounds we prepared, 22, i.e., 3a-3k and 4a-4k, were reported for the first time, while the preparation of 2a and 2b was reported in our recent paper. The cytotoxic activities of these compounds were evaluated against human chronic myeloid leukemia cells (K562) and a human nasopharynge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…To increase the antimicrobial properties of formononetin, formononetin derivatives in which the formononetin ring system was linked to the alkylamines by different spacers at C-7 position were investigated, with a view to modify their lipophilicity. Literature survey revealed that the compounds containing alkyl amino side chains showed better activities against the test bacteria than those containing aromatic ring amino side chains [15]. To further optimize this activity, seventeen compounds reported in this paper contain alkyl amino groups.…”
Section: Chemical Synthesismentioning
confidence: 93%
See 1 more Smart Citation
“…To increase the antimicrobial properties of formononetin, formononetin derivatives in which the formononetin ring system was linked to the alkylamines by different spacers at C-7 position were investigated, with a view to modify their lipophilicity. Literature survey revealed that the compounds containing alkyl amino side chains showed better activities against the test bacteria than those containing aromatic ring amino side chains [15]. To further optimize this activity, seventeen compounds reported in this paper contain alkyl amino groups.…”
Section: Chemical Synthesismentioning
confidence: 93%
“…Compounds 2a-c were the key intermediates for the synthesis of the compounds investigated. They were prepared from alkylation of 7-OH group by using 1,2-, 1,3-, or 1,4dihaloalkanes in the presence of K 2 CO 3 in anhydrous DMF [15]. The synthesis of compounds 3a-f, 4a-e, and 5a-f was accomplished according to the general pathway illustrated in Scheme 1.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…The chemical structures of natural products that inhibit MDM2 expression. derivatives have been shown to have remarkable cytotoxicity in in vitro screening studies, and may be promising for the development of new anticancer chemotherapeutics [171][172][173]. However, it is currently unknown if these genistein derivatives have MDM2 inhibitory effects.…”
Section: Flavonoids and Isoflavonoidsmentioning
confidence: 97%
“…Genistein also increases p21 expression levels, thereby inhibiting uncontrolled proliferation [133]. Encouraged by the excellent anticancer activity of genistein, several semisynthetic analogs such as synthetic genistein glycosides and 7-O-modified genistein derivatives are being developed as anticancer agents [136]. One of the biggest problems with development of genistein as an effective chemopreventive agent is its low oral bioavailability, which may also be responsible for its unclear therapeutic effects and large inter-individual variations in clinical trials.…”
Section: Genisteinmentioning
confidence: 99%
“…Among isoflavones, the major constituents that are majorly involved in cancer prevention and therapy include genistein and diadzein [129]. Genistein influences multiple biochemical functions in living cells, including activation of PPARs (peroxisome proliferator-activated receptors), inhibition of tyrosine kinases, inhibition of topoisomerases, and induction of autophagy [130][131][132][133][134][135][136]. Evidence of the anti-proliferative activity of genistein in vitro stems from its ability to inhibit the tyrosine kinase enzyme that is most often upregulated in cancer cells [130].…”
Section: Genisteinmentioning
confidence: 99%